Critical Synthesis Package: Revised Two-Factor Study Process Questionnaire (R-SPQ-2F) - Angela Hairrell (Association of American Medical Colleges, 2013)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the Revised Two-Factor Study Process Questionnaire (R-SPQ-2F), and (2) a copy of the R-SPQ-2F instrument and scoring key developed by John Biggs, PhD. The R-SPQ-2F is a 20-item questionnaire used to identify tertiary students' metacognitive approaches to learning in a classroom or research setting. The current version has two scales: Deep Approach and Surface Approach, as well as four subscales: Deep Motive, Deep Strategy, Surface Motive, and Surface Strategy. Students respond to questionnaire items using a 5-point Likert response scale (1 = never or only rarely true of me, 5 = always or almost always true of me). Raw scores are computed by summing the mean score for items identified for each subscale. Scores for Deep Approach and Surface Approach are the sums of the corresponding subscales. The length and ease of administration is a plus for this instrument. A clear disadvantage is the time required to score this measure, especially if using it with a large number of students or sample size. In sum, this measure has promise in the field of health care education, but requires additional validation with individuals at all levels given its limited use in the field of health care.